History of the komi-permyak writing system: a comparative overview of alphabets from the late 19th to the mid-20th century - Chernykh I.А. (Perm Federal Research Centre Journal, 2026)
This article presents a comparative historical analysis of alphabets developed for the Komi-Permyak language from the 19th century until the adoption of the modern Cyrillic standard in 1938. The relevance of the study stems from the lack of comprehensive works that systematize the numerous and often uncommon variants of its writing system in the scholarly literature. The aim of the work is to conduct a comparative analysis of these systems based on the criteria of adequacy in representing Komi-Permyak sounds, as well as the practicality and consistency of graphic solutions. The research material comprises alphabets from key monuments of Komi-Permyak writing: N. Rogov’s dictionary (1869), a series of primers (1894–1908), V. Molodtsov’s original Cyrillic alphabet (1918), Latin-based projects (1924, 1932), and projects for a Cyrillic alphabet from 1937. To ensure an objective comparison, the article first provides a detailed overview of the phonetic system of the Permic languages, including consonantism, vocalism, and main dialectal differences. The study identifies the main trends in the evolution of Komi-Permyak writing: from early projects that were guided by the rules of Russian orthography and often ignoring the language’s specificity, through strictly phonemic systems (the Savvaitov-Rogov, Molodtsov, and Latinized alphabets), to the modern alphabet, which represents a compromise between the phonemic principle and an orientation towards the Russian graphic base. The article contributes to the systematization of knowledge on the history of KomiPermyak writing and assesses the effectiveness of the considered alphabetic systems from linguistic and practical points of view.